Thermomechanical Fatigue Damage Model for Life prediction of Navel Copper Alloy - J.Al-Alkawi, Hussain; Abbas Al-Saraf, Saad; A.A Mohammed, Kafel (Anbar Journal of Engineering Sciences, 2011)
TMF (thermomechanical fatigue) damage model devoted to prediction of the high temperature fatigue lifetime of navel copper alloy (C46400) , was proposed .This model was built on the basis of the stress –number of cycles curve responsible for damage due to interaction of high temperature and fatigue. This obtained prediction compared was very favorably with the cumulative experimental TMF results.